ANALISIS SOSIOLOGI OLAHRAGA TERHADAP LOYALITAS SUPORTER SEPAK BOLA DI INDONESIA: STUDI LITERATUR - Siregar, Yan Indra; Arima, Putra; Harahap, Rinaldi Azhari; Imanuel P. Gurusinga; Purba, Hot Pardomuan; Romadona, Syahrul; Hutabarat, Angga P; Lumbanraja, Wander Juan Felix; Suranta, David Eikel; P. Oroh, Mhd Fahriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the loyalty of football supporters in Indonesia from the perspective of sports sociology. The research method used is a literature study with a descriptive qualitative approach by collecting data from various national journals published within the last 10 years. The results show that the loyalty of football supporters in Indonesia is formed through social solidarity, group identity, sense of belonging to the club, as well as the influence of culture and social media. This loyalty is reflected through consistent support for the club, both directly in the stadium and through communities and digital media. Besides providing positive impacts such as the formation of social solidarity and social community activities, supporter loyalty can also create negative impacts in the form of excessive fanaticism and conflicts between supporters. From the perspective of sports sociology, the phenomenon of supporter loyalty shows that football has become an important part of Indonesian social life. Therefore, it is necessary to instill the values of sportsmanship, tolerance, and social control so that supporter loyalty can provide positive contributions to the development of national football.